The Effect of pH and Sodium Silicate Dosage on the Separation of Magnesium and Lithium from Artificial Brine Water Using Chemical Precipitation Techniques - Lalasari, Latifa Hanum; Sulistiyono, Eko; Harjanto, Sri; Irawan, Januar; Firdiyono, Florentinus; Arini, Tri; Andriyah, Lia; Suharyanto, Ariyo; Natasha, Nadia Chrisayu; Yunita, Fariza Eka (Metalurgi, 2023)
This study aims to report the findings of an investigation into the separation of lithium and magnesium ions in the artificial brine water. The artificial brine water contains concentrations of magnesium, calcium, and lithium cations that closely resemble the concentrations seen in natural brine water sourced from Gunung Panjang using magnesium chloride, calcium chloride, and lithium chloride p.a. The objective of this experiment was to investigate the impact of pH and the addition of sodium silicate on the separation of magnesium and calcium ions from lithium ions in artificial brine water. The best outcomes were achieved when the pH of the brine water was set at 10, and sodium silicate was added in a stoichiometric ratio of 219%. These parameters led to a lithium content of 90.06%, magnesium removal of  70.32%, and a Mg/Li ratio of 6.29, indicating a substantial presence of magnesium ions precipitated as solids with pyroxene (MgSiO3) phase. This research also succeeded in increasing the lithium content by 94.28% and reducing the Mg/Li ratio to 4.96 after the precipitated solids were subjected to a water-leaching process.